Editorial: Reflecting on Culturally Responsive Teaching and Learning, Supporting Indigenous and International Learners - Katie Archer Olson; Thomas D. Dyer (Journal of Scholarly Engagement)
As we approach the halfway point of 2023, it is time to reflect on the progress that has been made in the field of scholarly engagement. In recent years, there has been a growing recognition of the importance of engaging with the public in order to promote the impact of scholarly research. One of the most important aspects of scholarly engagement is the need to communicate research findings in a way that is accessible and engaging to the public.